Linkages between Soil Security and One Health: implications for the 2030 Sustainable Development Goals - Swan, Tom; McBratney, Alex; Field, Damien (Frontiers in Public Health, 2024)
Soil provides multiple and diverse functions (e.g., the provision of food and the regulation of carbon), which underpin the health of animals, humans, the environment and the planet. However, the world’s soils face existential challenges. To this end, the concept of Soil Security was developed, compelled to: “maintain and improve soils worldwide so that they can continue to provide food, fiber and fresh water, contribute to energy and climate sustainability and help to maintain biodiversity and the overall protection of ecosystem goods and services.” In parallel, the concept of One Health likewise works across the human–animal–environment interface, highly relevant for the goals of Soil Security. In this review, we evaluated the roles which both the Soil Security and One Health concepts have served in the literature between 2012 and 2023 and explore the potential linkages between both concepts. We outline that both concepts are used in disparate fields, despite considerable overlap in aims and objectives. We highlight the Soil Health concept as a potential connector between Soil Security and One Health. Overall, we argue that both Soil Security and One Health are highly complementary fields of scientific inquiry with solid leverage for translation into policy and practice. However, there is a need to define One Health dimensions, as has been done for Soil Security. As such, we proffer five measurable dimensions for One Health, the “5Cs”–Capacity, Condition, Capital, Connectivity and Codification–to allow for an overall measure of One Health. Finally, we advocate for a biosphere-focused framework to collectively make progress toward the 2030 Sustainable Development Goals and other global existential challenges.